Reexamining possible mispricing of customer satisfaction - David R. Bell; Olivier Ledoit; Michael Wolf (University of Zurich, Department of Economics, 2012)
There has been a recent debate in the marketing literature concerning the possible mispricing of customer satisfaction. While earlier studies claim that portfolios with attractive out-of-sample properties can be formed by loading on stocks whose firms enjoy high customer satisfaction, later studies challenge this finding. A large part of the disagreement stems from the difficulty of how to actually evaluate mispricing based on the observed portfolio returns. In particular, any portfolio formation method that requires the use of a risk model is open to the criticism of time-varying risk factor loadings due to the changing composition of the portfolio over time. As an alternative, we construct portfolios that are neutral with respect to the desired risk factors a priori. Consequently, no risk model is needed when analyzing the observed returns of our portfolios. Using various ways of measuring customer satisfaction, we do not find any convincing evidence that portfolios that load on high customer satisfaction lead to abnormal returns.
Keywords: G11; G12; 330; customer satisfaction; financial performance; long-short portfolio; mispricing